Dakwah dan Hukum Lingkungan - Acep Aripudin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2008)
The most important of Central isue in global era is global  warning effect. One of its’causes is  hyper-using  of technology un-controlled, that become damage in this world. The other causes is un-controlled of  exploitation to nature and is not be attend to ecosystem and environment live. Respons and reaction to global condition was spoken by a lot of people, --include – Islam, specially if looked according to Islamic law. Masalah-mursalah concept, as teoritic can be made basic in  giving solution  this global accident.